Frugivory and Seed Dispersal of the Threatened Cactus Browningia candelaris in the Vicinity of a Mining Site in the Atacama Desert, Chile - Ana María Humaña; Carlos E. Valdivia (Diversity)
Mining is an indispensable activity that threatens biodiversity globally. However, assessments of key ecological processes for the maintenance of plants threatened by mining, such as the effectiveness of frugivory and seed dispersal, are almost non-existent. We evaluated the effectiveness of fruit and seed dispersal in the threatened cactus Browningia candelaris at two different sites: one distant and one close to a mining company currently in operation. Unfortunately, in the study area, B. candelaris is only present in the two evaluated sites, which makes it impossible to have replications for the distant and nearby sites. With this caveat in mind, we evaluated the different parameters of dispersal effectiveness by comparing both sites, far and close to the copper mine. Fruit abundance was significantly higher near the mine. By contrast, animal richness was lower near the mine. However, animal visitation rates for consumption of immature and mature fruits did not differ significantly between sites. Of the 15 animals observed, only four consumed and defecated live seeds: the fox Lycalopex culpaeus, the lizard Microlophus theresioides, and the mouse Octodontomys gliroides and Phyllotis xantopygus. Seed dispersal effectiveness was higher near the mine, but extremely low at both sites. In fact, population recruitment of new cacti was null at both sites, near and far from the mine, due to the scarcity of water in the environment. This is probably due to the increasing aridity of the Atacama Desert due to global warming. Therefore, new studies to assess synergies between potential local threats, such as mining operations, and global threats, such as global warming, are essential to carry out relevant conservation actions on endangered species such as cacti.